Carbon footprint and climate risk of most consumed food products in Cali, Colombia Methodological development of a decision support tool - Gerbal, Lisa (International Center for Tropical Agriculture, 2019)
Cali, home to nearly 2 million of inhabitants, is growing, and with it the impacts of its urban population on the environment through the high demand and use of food , water, and energy. Changing climate is also threatening the provision of food and the food systems in general. In this context, CIAT’s Sustainable Food Systems (SFS) research program aims to develop tools and methods to better analyze the interactions between food systems, human health and ecological systems. This study aimed at developing a methodological approach to better assess, understand, and use information on environmental sustainability and resilience of highly consumed products in a city. A combined methodology was used to simultaneously assess the impacts of food on the environment (Carbon footprint ) and the impacts of projected changes i n climate patterns on the suitability for food crops production, for the top five food products consumed in Cali , department of Valle del Cauca, Colombia.